Redefining Norms: A Study of Margaret Atwood's The Year of The Flood - Ali, Muhammad Ilham (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze literary theories and approaches that can be applied in Margaret Atwood’s works, one of her novels entitled The Year of The Flood. This issue or social phenomena of the pandemic and post-pandemic era in the novel reflected by Atwood was remarkable; the image and the moral values in the book remain toward humans universally. This study’s literary approach is ‘Mimetic Theory’ by M.H Abrams, which analyzes social aspects as a real-life reflection. A descriptive qualitative method was applied in this study. The data consists of both primary data and supporting data. The main dates were mainly from the novel The Year of The Flood by Atwood (2009). The supporting data were from reference books, journals, and articles related to the research. In the final result, there were five aspects, namely the environments, feelings, economic factors, crime, and faith, which were related and analyzed using mimetic theory